Remote Intracerebral Hemorrhage After Intravenous Thrombolysis: Results From a Multicenter Study. Issue 8 (August 2016) - Prats-Sánchez, Luis; Camps-Renom, Pol; Sotoca-Fernández, Javier; Delgado-Mederos, Raquel; Martínez-Domeño, Alejandro; Marín, Rebeca; Almendrote, Miriam; Dorado, Laura; Gomis, Meritxell; Codas, Javier; Llull, Laura; Gómez González, Alejandra; et al.
Abstract : Background and Purpose—: Remote parenchymal hemorrhage (rPH) after intravenous thrombolysis with recombinant tissue-type plasminogen activator may be associated with cerebral amyloid angiopathy, although supportive data are limited. We aimed to investigate risk factors of rPH after intravenous thrombolysis with recombinant tissue-type plasminogen activator. Methods—: This is an observational study of patients with ischemic stroke who were treated with intravenous thrombolysis with recombinant tissue-type plasminogen activator and were included in a multicenter prospective registry. rPH was defined as any extraischemic hemorrhage detected in the follow-up computed tomography. We collected demographic, clinical, laboratory, radiological, and outcome variables. In the subset of patients who underwent a magnetic resonance imaging examination, we evaluated the distribution and burden of cerebral microbleeds, cortical superficial siderosis, leukoaraiosis, and recent silent ischemia in regions anatomically unrelated to the ischemic lesion that caused the initial symptoms. We compared patients with rPH with those without rPH or parenchymal hemorrhage. Independent risk factors for rPH were obtained by multivariable logistic regression analyses. Results—: We evaluated 992 patients (mean age, 74.0±12.6 years; 52.9% were men), and 408 (41%) of them underwent a magnetic resonance imaging. Twenty-six patients (2.6%) had a rPH, 8 (0.8%) had both rPH and PH, 58 (5.8%) had PH, and 900 (90.7%) had no bleeding complication. Lobar cerebral microbleeds (odds ratio, 8.0; 95% confidence interval, 2.3–27.2) and recent silent ischemia (odds ratio, 4.8; 95% confidence interval, 1.6–14.1) increased the risk of rPH. Conclusions—: The occurrence of rPH after intravenous thrombolysis with recombinant tissue-type plasminogen activator in patients with ischemic stroke is associated with lobar cerebral microbleeds and multiple ischemic lesions in different regions. Abstract : Supplemental Digital Content is available in the text.